Factors Affecting Land and Building Tax Revenue in Ambon City - Usi Marsya Latuihamallo; Dientje Rumerung; Muhammad Bugis; Fahrudin Ramly (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
This study aims to analyze the Factors affecting Land and Building Tax Revenue in Ambon City. This type of research is quantitative with the type of data used is secondary data with data sources obtained from the Ambon City Tax and Retribution Management Agency and the Central Statistics Agency Publication. The method of data collection carried out is by documentation. The data analysis method used is the multiple regression analysis method. The results showed that, partially, per capita income and population had a significant effect on Land and Building Tax revenues while inflation did not have a significant effect on Land and Building Tax revenues. Simultaneously, per capita income, population, and inflation together have a significant effect on Land and Building Tax revenue in Ambon City.